2020
DOI: 10.1007/s10800-019-01379-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic exfoliation of carbon fiber: electroanalytical perspectives

Abstract: Electrochemical anodisation techniques are regularly used to modify carbon fiber surfaces as a means of improving electrochemical performance. A detailed study of the effects of oxidation (+ 2 V) in alkaline media has been conducted and Raman, XPS and SEM analyses of the modification process have been tallied with the resulting electrochemical properties. The co-application of ultrasound during the oxidative process has also been investigated to determine if the cavitational and mass transport features influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
4
13
0
Order By: Relevance
“…The ultrasound treatments’ ability to increase oxygenated functional groups, improving the charge-transfer capacity on nanofibers, has been reported . This observation further confirms the positive role of the LPE proposed here, since often chemical and physical activator treatments are needed to obtain carbon nanofibers with useful electrochemistry.…”
Section: Resultssupporting
confidence: 85%
“…The ultrasound treatments’ ability to increase oxygenated functional groups, improving the charge-transfer capacity on nanofibers, has been reported . This observation further confirms the positive role of the LPE proposed here, since often chemical and physical activator treatments are needed to obtain carbon nanofibers with useful electrochemistry.…”
Section: Resultssupporting
confidence: 85%
“…As suggested by some authors, the surface shown in Fig. 4a is proposed, which is in agreement with the H2SO4 treatment performed in this study [34,35,37,40,41,42,43].…”
Section: Characterization Of the Carbon Cloth Electrodesupporting
confidence: 92%
“…3a, revealing the appearance of peak Ia in the anodic direction (oxidation). The appearance of this signal can be attributed to the oxidation of electrochemically active functional groups on the surface because of treatment with H2SO4 [34], such as quinones, aldehydes, or carboxylic acids [35,36,37]. Reversing the scanning in a cathode sense (reduction) reveals peak Ic, assigned to the reduction of electrochemically active functional groups on the surface.…”
Section: Characterization Of the Carbon Cloth Electrodementioning
confidence: 99%
“…Band G is a characteristic peak of sp 2 carbon in the graphitic structure. Band 2D, located at 2690 cm −1 , is a combination of bands D and G and is also a characteristic band of the graphitic carbon 47 , 48 . As can be seen, the spectrum of the original CF is relatively weak, but it sharply increases after modification, indicating that the structure of the carbon fiber has changed.…”
Section: Resultsmentioning
confidence: 99%